Sierra Mejía, R. (compilador). (1985). La fílosofía en Colombia. (Siglo XX). Bogotá: Nueva biblioteca colombiana de Cultura. Procultura. Presidencia de la República. 251 págs. - Hoyos Jaramillo, Luis Eduardo; Pontificia Universidad Javeriana (2016)
null